SOME POST-LARVAL AND JUVENILE STAGES OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER), WITH NOTES ON THE CHANGES IN BODY FORM - Balakrishnan, V; Rao, K V Narayana (Indian Journal of Fisheries, 2011)
The Indian mackerel, Rastrelliger kanagurta (Cuvier), belonging to the familyScombridae, is one of the commercially important food fishes of India anda few other countries bordering the Indo-Pacific. The life history of this specieshas not been fully investigated so far.The earliest description of a Rastrelliger egg is by Delsman(1926) from theJava Sea. Subsequently, Delsman (1931) expressed doubts about the .correctnessof his earlier identification. Manacop (1956) has described, from the Philippinewaters, two specimens of R. chrysozonus measuring 26 mm and 48 mm in length.Devanesen and John (1940), Balakrishnan (1957) and Kuthalingam (1956) haverecorded the occurrence of eggs and larvae of R. kanagurta from the Indian waters.Jones and Kumaran (1964) have given figures of two juveniles measuring 34 mmand 65 mm in length. A single larva measuring 9.3 mm collected from theAndaman Sea during Vityaz Expedition has been described by Gorbunova (1963).The eggs and larvae of Rastrelliger, collected from the Gulf of Thailand, havebeen described by Boonprakob (1962, 1965) and the Rastrelliger larvae collectedfrom the same area during the Naga Expedition have been described by Matsui(1963).In this paper a series of early stages of the Indian mackerel ispresented. However, this does not include the pro-larvae reported earlier {videBalakrishnan, 1957) as the material is not available now.